A case of multiple thrombosis and septic shock in a critically ill patient with Omicron infection. Issue 11 (November 2022) - Jin, Shanshan; Luo, Jian; Wu, Xiayun; Wang, Danqiong; Zhang, Weiwen; Li, Zhangping
Abstract: The emergence of the acute respiratory syndrome coronavirus 2 variant named Omicron has become a global concern. A 74-year-old unvaccinated patient was critically ill infected with the Omicron variant characterised by septic shock, large-scale cerebral embolism, deep vein thrombosis, and multiple organ dysfunction with respiratory failure, acute renal failure, coagulation dysfunction. The clinical symptoms were successfully controlled by active rescue treatment such as anti-infection, anti-shock, implantation of a vena cava filter as well as multi-organ function support. Although there are many complications in critically ill patients with Omicron variant infections, especially coagulation disorders and thrombosis, they can be resolved with a combination of Chinese and Western medicine positive rescue.